Hambatan Belajar Matematika Di Kelas Inklusi: Perspektif Siswa Tunarungu Dan Guru - Afra Fadhila, Yoan; Izzatika, Anna Fi; Putranto, Sumbaji (JPI (Jurnal Pendidikan Inklusi), 2023)
This study describe teachers and students with deafblindness perceive the difficulties of learningmathematics in the inclusive classroom. The purpose of this study was to find the problems facedby both of them when learning mathematics in the inclusive classroom. This study used adescriptive qualitative approach with data collection through observation, interviews, anddocumentation. Two deaf students and two maths teachers who teach in the inclusive class wereinvolved in this study. The results of the study, it can be concluded that in the learning process inthe inclusion class there are obstacles that come from internal factors, in the implementation oflearning, and social factors. The lack of encouragement and interest of deaf students to learnmathematics is the main obstacle for students and teachers. Meanwhile, some of the challengesfaced by students include the teacher's difficulty in choosing various learning approaches,processing materials for deaf students, each of whom has a different level of ability, the lack ofavailability of learning media and facilities provided by the school, and the lack of specialassistant teachers at school.Keywords: Learning Disabilities, Math, Inclusive Class, Deaf Student, Teacher